Corrosion Behaviour of Aluminium Alloy 7020-T6 welded Joint in Sea Water at Different Variables - Huda Mohammed Abdulaziz (Engineering and Technology Journal, 2013)
were welded by using inert gas metal arc welding method (MIG)to obtain butt joint with geometry of single V at 45⁰with two pass. The joints were tested by X-ray radiography and faulty pieces were excluded.and the indefectible joints were subjected to stress relief heat treatment including heating the joint to evaluating temperature 100 C⁰for one hour and air cooling.Optical microscopy with camera was used to observe the welded joint microstructure.Micro hardness test were carried out using Vickers instrument to measure the hardness of the welded joint. Corrosion behavior of welded jointspecimens in 3.5% NaCl solution at different media velocity (1, 2, 3) m/min and temperature of (25, 50, 75) ⁰ C for each velocitywas examined using Tafelpolarization measurements. It is determined byopen circuit potential (OCP) after that the cell’s current is changed due to the increasing in potentialby ±100mV to calculate corrosion current then corrosion rate. The results show that the corrosion rate is increased with increasing solution temperature. This is because of the prevention of oxygen from dissolving in water, while the corrosion rate decreases with increasing velocity of sea water since the movement of the liquid prevents the formation of deposits and ions gathering on cathode pole where corrosion can easily develop. when comparing corrosion rate between the welded and unwelded samples, the welded samples gives more corrosion rate value since the cycle of heating and cooling that occurs during the welding process affects the microstructure of welds.